Preparing for transitions - Collins, D.; MacNamara, A. (Talent development: A practitioner guide, 2018)
Young athletes must meet the challenge of combining study and sport as they progress along the development pathway. Managing this dual career of combining a sporting career with studies or, for older athletes work, is a source of concern for many developing and high-performance athletes. The relevance of the dual career points to the need to consider the support and resources that young athletes need as they attempt to negotiate these transitions. This chapter provides guidelines and resources for athletes, their parents and coaches to help them pre-empt potential challenges associated with this dual career, develop the skills to negotiate and benefit from this transition, and understand and implement the support structures required to minimise disruptions to both elements of the dual career. The young athlete who is equipped with the skills to successfully cope with these challenges, and offered the required support systems, will be able to balance this dual-career successfully.